A born‐digital field‐to‐database solution for collections‐based research using collNotes and collBook. (23rd August 2019) - Powell, Caleb; Motley, Jacob; Qin, Hong; Shaw, Joey
Abstract : Premise: The digitization of natural history collections includes transcribing specimen label data into standardized formats. Born‐digital specimen data initially gathered in digital formats do not need to be transcribed, enabling their efficient integration into digitized collections. Modernizing field collection methods for born‐digital workflows requires the development of new tools and processes. Methods and Results: collNotes, a mobile application, was developed for Android and iOS to supplement traditional field journals. Designed for efficiency in the field, collNotes avoids redundant data entries and does not require cellular service. collBook, a companion desktop application, refines field notes into database‐ready formats and produces specimen labels. Conclusions: collNotes and collBook can be used in combination as a field‐to‐database solution for gathering born‐digital voucher specimen data for plants and fungi. Both programs are open source and use common file types simplifying either program's integration into existing workflows.